BAHAYA DISINTEGRASI BANGSA AKIBAT OTONOMI DAERAH PADA MASA MATARAM ISLAM - Sambung Widodo (Berkala Arkeologi, 2003)
During the reign of the Islamic Mataram Kingdom, the reign of the king was actually a hierarchical relationship between independent, highly autonomous and self-sufficient units of power, which were vertically connected by individual ties among several power holders (regents). Apart from the connecting bonds in the form of devotion and loyalty to the same person, namely the king, it seems that there is no horizontal administrative relationship that can ensure or protect the independence of the regents from one another. In reality, it is easy to take arbitrary actions against fellow royal officials when the oversight power of the central government becomes weak. Such a situation tempted the king's officials (regents) to act arbitrarily against each other, because the autonomy granted to officials (regents) was accompanied by the right to have their own armed forces.